Radiofrequency-triggered release for on-demand delivery of therapeutics from titania nanotube drug-eluting implants. (August 2014) - Bariana, Manpreet; Aw, Moom Sinn; Moore, Eli; Voelcker, Nicolas H; Losic, Dusan
Aim: This study aimed to demonstrate radiofrequency (RF)-triggered release of drugs and drug carriers from drug-eluting implants using gold nanoparticles as energy transducers.Materials & methods: Titanium wire with a titania nanotube layer was used as an implant loaded with indomethacin and micelles (tocopheryl PEG succinate) as a drug and drug carrier model. RF signals were generated from a customized RF generator to trigger in vitro release.Results & discussion: Within 2.5 h, 18 mg (92%) of loaded drug and 14 mg (68%) of loaded drug carriers were released using short RF exposure (5 min), compared with 5 mg (31%) of drug and 2 mg (11%) of drug carriers without a RF trigger. Gold nanoparticles can effectively function as RF energy transducers inside titania nanotubes for rapid release of therapeutics at arbitrary times.Conclusion: The results of this study show that RF is a promising strategy for triggered release from implantable drug delivery systems where on-demand delivery of therapeutics is required. Original submitted 19 November 2012; Revised submitted 1 April 2013